Self-filling hydrophobic hydrogel microcapsules, and preparation method and application thereof
Patent Information
- Application Number
- CN202611293200.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-25
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]本发明针对普通缓释型疏水微胶囊虽可实现水泥基材料后期疏水改性,但可能引起局部孔隙增加、界面疏松和中后期强度折损的问题,提供一种兼具延迟疏水调控和局部孔隙自填充功能的自填充型疏水水凝胶微胶囊及其制备方法与应用
[0025] 1. By co-coating hydrophobic components with reactive silicon sources, the slow-release hydrophobicity and pore self-filling of cement-based materials can be synergistically regulated.
Smart Images

Figure CN122916504A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of cement-based material durability regulation technology, specifically relating to a self-filled hydrophobic hydrogel microcapsule, its preparation method, and its application. Background Technology
[0002] Cement-based materials contain capillary pores and interconnected pores. Moisture and corrosive media such as chloride ions carried by it can migrate into the material's interior along the pore network, leading to steel corrosion, freeze-thaw damage, and decreased durability. While adding hydrophobic agents directly to the mixing system can reduce the wettability of the pore walls, the hydrophobic components may coat unhydrated particles upon early contact with cement particles, interfering with the hydration reaction and interfacial structure formation, thus causing a loss of mechanical properties.
[0003] The use of polyvinyl alcohol / sodium alginate hydrogel microcapsules to encapsulate hydroxyl-terminated polydimethylsiloxane allows for delayed release of hydrophobic components through the gradual relaxation of the capsule wall in a cement-based, strongly alkaline, and humid environment. This enables the material to maintain hydrophilicity and normal hydration in the early stages, while gradually establishing overall hydrophobicity in the later stages. However, conventional slow-release hydrophobic microcapsules, as excipients, alter the original packing state of the slurry and form new interface regions between the microcapsules and the cement matrix. Furthermore, the release of the core material may leave localized cavities, leading to increased porosity, increased interconnected channels, and strength loss in the later stages.
[0004] Therefore, it is necessary to introduce self-filling components that can undergo subsequent reactions in a cement-based strong alkaline environment on the basis of the original sustained-release hydrophobic microcapsules. This would enable the microcapsules to not only regulate the wettability of the pore walls, but also to provide structural compensation for the microcapsule surroundings, the core material release path, and local pore defects, thereby reducing the pore structure and strength costs of ordinary sustained-release microcapsules. Summary of the Invention
[0005] This invention addresses the problem that while conventional sustained-release hydrophobic microcapsules can achieve late-stage hydrophobic modification of cement-based materials, they may cause increased local porosity, loose interfaces, and reduced strength in the mid-to-late stages. It provides a self-filling hydrophobic hydrogel microcapsule that combines delayed hydrophobic regulation and local pore self-filling functions, along with its preparation method and applications.
[0006] The present invention adopts the following technical solution:
[0007] In a first aspect, the present invention provides a self-filled hydrophobic hydrogel microcapsule, the microcapsule comprising a core material and a capsule wall covering the core material; the capsule wall is a hydrogel network formed by double crosslinking of polyvinyl alcohol and sodium alginate, and the core material is a composite core material composed of hydroxyl-terminated polydimethylsiloxane and tetraethyl orthosilicate.
[0008] Secondly, the present invention provides a method for preparing self-filled hydrophobic hydrogel microcapsules and cement-based materials, comprising the following steps:
[0009] Step 1: Prepare polyvinyl alcohol aqueous solution and sodium alginate aqueous solution separately, and mix them thoroughly to obtain polyvinyl alcohol / sodium alginate hydrogel precursor solution;
[0010] Step 2: Hydroxyl-terminated polydimethylsiloxane and tetraethyl orthosilicate are uniformly mixed to obtain a hydrophobic-self-filled composite oil phase;
[0011] Step 3: Add the emulsifier to deionized water to form an emulsified aqueous phase. Under stirring conditions, add the composite oil phase dropwise to the emulsified aqueous phase for emulsification to obtain a composite emulsion.
[0012] Step 4: Add the composite emulsion to the hydrogel precursor solution and mix evenly to obtain a capsule-forming precursor solution containing the composite core material.
[0013] Step 5: Add the capsule-forming precursor solution dropwise into the calcium chloride solution, allowing sodium alginate to pass through the Ca... 2+ Hydrogel microbeads are formed through primary ionic cross-linking.
[0014] Step 6: Transfer the hydrogel microbeads to a boric acid solution to allow polyvinyl alcohol to undergo secondary cross-linking. Then collect, wash and dry to obtain the self-filled hydrophobic hydrogel microcapsules.
[0015] Further, in step 1, the mass-volume concentration of the polyvinyl alcohol aqueous solution is 4.0%-8.0%, and the mass-volume concentration of the sodium alginate aqueous solution is 2.0%-4.0%; the dry basis mass ratio of polyvinyl alcohol to sodium alginate is 1:1-4:1, preferably 2:1.
[0016] Further, in step 2, the mass ratio of hydroxyl-terminated polydimethylsiloxane to tetraethyl orthosilicate is 92:8-100:10; the two are mixed at 15-35 °C and 100-800 r / min for 1-30 min, preferably at 25 °C and 300 r / min for 5 min.
[0017] Further, in step 3, the emulsifier is alkylphenol polyoxyethylene ether; the emulsifier is dissolved at 15-35 ℃ and 500-1200 r / min for 5-20 min, then the stirring speed is increased to 1200-2200 r / min and emulsified for 10-40 min, and then allowed to stand for 1-5 h to remove bubbles.
[0018] Further, in step 5, the mass concentration of the calcium chloride solution is 4%-8%, preferably 6%; in step 6, the mass concentration of the boric acid solution is 3%-7%, preferably 5%, and the pH of the boric acid solution is adjusted to 8-9 using sodium hydroxide, and the secondary crosslinking is completed under conditions of 20-25 °C and gentle stirring.
[0019] Thirdly, the present invention provides a cement-based material containing the aforementioned self-filled hydrophobic hydrogel microcapsules.
[0020] Furthermore, the amount of microcapsules is 0.1%-3.0% of the mass of the cementitious material, preferably 0.5%; the water-cement ratio of the cementitious material is 0.30-0.60;
[0021] Fourthly, the present invention provides a method for preparing the above-mentioned cement-based material, wherein the cementitious material and the microcapsules are first dry-mixed, then mixed with mixing water and mechanically stirred, and then cured after molding.
[0022] Furthermore, after the self-filled hydrophobic hydrogel microcapsules are added to the cement-based material, the hydroxyl-terminated polydimethylsiloxane migrates to the pore wall of the cement-based material after the microcapsule wall relaxes and reduces the wettability of the pore wall. Tetraethyl orthosilicate hydrolyzes and condenses in a strongly alkaline and humid environment to form a structure containing Si-O-Si bonds, thereby compensating for structural defects around the microcapsules, the core material release path, and local pore defects.
[0023] The microcapsules and cement-based materials described in this invention can be widely used in conventional cement-based materials such as buildings, bridges, tunnels, underground engineering and marine engineering, and can also be used in cement rings or cement-based sealing structures for underground wells such as oil wells, gas wells and carbon dioxide storage wells.
[0024] The beneficial effects of this invention are as follows:
[0025] 1. By co-coating hydrophobic components with reactive silicon sources, the slow-release hydrophobicity and pore self-filling of cement-based materials can be synergistically regulated.
[0026] 2. The use of a double-crosslinked hydrogel capsule wall reduces the interference of functional components on early hydration and allows for gradual release in the middle and late stages, forming a time-response effect.
[0027] 3. While improving the resistance to water absorption and chloride ion penetration, it reduces the pore defects and strength loss caused by microcapsules, achieving a coordinated improvement in durability and mechanical properties. Attached Figure Description
[0028] Figure 1 This is a microscopic mechanism diagram of a self-filling hydrophobic hydrogel microcapsule proposed in this invention.
[0029] Figure 2 Figures show the compositional and structural characterization results of ordinary microcapsules and self-filled microcapsules, where (a) is the Fourier transform infrared spectroscopy result, (b) is the X-ray diffraction result, and (c) is the scanning electron microscopy-energy dispersive spectroscopy result.
[0030] Figure 3 The image shows the surface contact angle results of cement paste specimens at different ages.
[0031] Figure 4 The image shows the chloride ion penetration depth of cement paste specimens at different ages.
[0032] Figure 5 The graph shows the porosity results of cement paste specimens after 60 days.
[0033] Figure 6 The images show three-dimensional reconstructions of cement paste specimens obtained by X-ray computed tomography at 60 days, where (a) represents the CG group, (b) the OMG group, and (c) the SMG group.
[0034] Figure 7 The graph shows the compressive strength results of cement paste specimens at different ages. Detailed Implementation
[0035] The present invention will now be described in detail with reference to specific embodiments. These embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention.
[0036] Example 1
[0037] like Figure 1 As shown, this invention provides a method for preparing self-filled hydrophobic hydrogel microcapsules, comprising the following steps:
[0038] (1) Preparation of polyvinyl alcohol / sodium alginate precursor solution. Polyvinyl alcohol powder was gradually added to deionized water and heated and stirred at 70 °C and 800 r / min for about 90 min to obtain a clear and homogeneous 4.0% (w / v) polyvinyl alcohol solution, which was then cooled to 25 °C. Sodium alginate powder was added to deionized water in batches and stirred at 80 °C and 1200 r / min for about 40 min to obtain a 2.0% (w / v) sodium alginate solution, which was then cooled to 25 °C. The two solutions were mixed at a dry basis mass ratio of 4:2 for polyvinyl alcohol to sodium alginate and stirred at 800 r / min for 10 min to obtain the hydrogel precursor solution.
[0039] (2) Preparation of hydrophobic-self-filled composite oil phase. At 25 °C, the two components were weighed according to m (hydroxyl-terminated polydimethylsiloxane): m (tetraethyl orthosilicate) = 92:8, and stirred magnetically at 300 r / min for 5 min in a closed container until homogeneous to obtain the composite oil phase.
[0040] (3) Preparation of composite emulsion. Alkylphenol polyoxyethylene ether was added to deionized water and stirred for 10 min at 25 ℃ and 800 r / min. Then the stirring speed was increased to 1600 r / min, and the above composite oil phase was slowly added dropwise to the emulsified aqueous phase. Emulsification was continued for 20 min to obtain a stable milky white composite emulsion. The emulsion was covered and allowed to stand for 3 h to remove bubbles, so as to reduce premature hydrolysis caused by the moisture absorption of tetraethyl orthosilicate.
[0041] (4) Double cross-linking encapsulation. The composite emulsion was added to the polyvinyl alcohol / sodium alginate precursor solution and mixed evenly. Then, it was added dropwise to a 6% calcium chloride solution to allow Ca to form encapsulation. 2+ The microcapsules underwent a primary ionic cross-linking with alginate to form hydrogel particles. The resulting gel beads were then transferred to a 5% boric acid solution for secondary cross-linking, and the pH of the system was adjusted to 9 using a 1.0 mol / L sodium hydroxide solution. The reaction was maintained at 25 °C with gentle stirring. After the secondary cross-linking was complete, the microcapsules were collected, designated SMG, washed three times with deionized water, and dried at room temperature for later use.
[0042] Comparative Example 1
[0043] This comparative example provides a method for preparing a conventional sustained-release hydrophobic microcapsule. The difference between this example and Example 1 is that tetraethyl orthosilicate is not added. This comparative example uses a polyvinyl alcohol / sodium alginate precursor solution and a double crosslinking encapsulation process, with hydroxyl-terminated polydimethylsiloxane as the sole core material. Specifically, the hydroxyl-terminated polydimethylsiloxane is pre-emulsified in an aqueous solution of alkylphenol polyoxyethylene ether. The resulting emulsion is then mixed uniformly with the polyvinyl alcohol / sodium alginate precursor solution, followed by primary ionic crosslinking and secondary crosslinking in a 6% calcium chloride solution and a 5% boric acid solution, respectively. The pH of the secondary crosslinking system is adjusted to 8-9. After the reaction is complete, the system is washed three times with deionized water and dried at room temperature.
[0044] Example 2
[0045] This invention provides a method for preparing self-filled hydrophobic hydrogel microcapsules, comprising the following steps:
[0046] (1) Preparation of polyvinyl alcohol / sodium alginate precursor solution. Polyvinyl alcohol powder was gradually added to deionized water and heated and stirred at 70 °C and 800 r / min for about 90 min to obtain a clear and homogeneous 4.0% (w / v) polyvinyl alcohol solution, which was then cooled to 25 °C. Sodium alginate powder was added to deionized water in batches and stirred at 80 °C and 1200 r / min for about 40 min to obtain a 4.0% (w / v) sodium alginate solution, which was then cooled to 25 °C. The two solutions were mixed at a dry basis mass ratio of 4:2 for polyvinyl alcohol to sodium alginate and stirred at 800 r / min for 10 min to obtain the hydrogel precursor solution.
[0047] (2) Preparation of hydrophobic-self-filled composite oil phase. At 35 °C, the two components were weighed according to m (hydroxyl-terminated polydimethylsiloxane): m (tetraethyl orthosilicate) = 100:10, and stirred magnetically at 100 r / min for 30 min in a closed container until homogeneous to obtain the composite oil phase.
[0048] (3) Preparation of composite emulsion. Alkylphenol polyoxyethylene ether was added to deionized water and stirred for 20 min at 35 ℃ and 500 r / min. Then the stirring speed was increased to 1200 r / min, and the above composite oil phase was slowly added dropwise to the emulsified aqueous phase. Emulsification was continued for 10 min to obtain a stable milky white composite emulsion. The emulsion was covered and allowed to stand for 1 h to remove bubbles, so as to reduce premature hydrolysis caused by the moisture absorption of tetraethyl orthosilicate.
[0049] (4) Double cross-linking encapsulation. The composite emulsion was added to the polyvinyl alcohol / sodium alginate precursor solution and mixed evenly. Then, it was added dropwise to a 4% calcium chloride solution to allow Ca to form encapsulation. 2+ The microcapsules underwent a primary ionic crosslinking with alginate to form hydrogel particles. The resulting gel beads were then transferred to a 3% boric acid solution for secondary crosslinking, and the pH of the system was adjusted to 9 using a 1.0 mol / L sodium hydroxide solution. The reaction was maintained at 25 °C with gentle stirring. After the secondary crosslinking was complete, the microcapsules were collected, washed three times with deionized water, and dried at room temperature for later use.
[0050] Example 3
[0051] This invention provides a method for preparing self-filled hydrophobic hydrogel microcapsules, comprising the following steps:
[0052] (1) Preparation of polyvinyl alcohol / sodium alginate precursor solution. Polyvinyl alcohol powder was gradually added to deionized water and heated and stirred at 70 °C and 800 r / min for about 90 min to obtain a clear and homogeneous 8.0% (w / v) polyvinyl alcohol solution, which was then cooled to 25 °C. Sodium alginate powder was added to deionized water in batches and stirred at 80 °C and 1200 r / min for about 40 min to obtain a 2.0% (w / v) sodium alginate solution, which was then cooled to 25 °C. The two solutions were mixed at a dry basis mass ratio of polyvinyl alcohol to sodium alginate of 4:2 and stirred at 800 r / min for 10 min to obtain the hydrogel precursor solution.
[0053] (2) Preparation of hydrophobic-self-filled composite oil phase. At 15 °C, the two components were weighed according to m (hydroxyl-terminated polydimethylsiloxane): m (tetraethyl orthosilicate) = 92:8, and stirred magnetically at 800 r / min for 1 min in a closed container until homogeneous to obtain the composite oil phase.
[0054] (3) Preparation of composite emulsion. Alkylphenol polyoxyethylene ether was added to deionized water and stirred for 5 min at 15 ℃ and 1200 r / min. Then the stirring speed was increased to 2200 r / min, and the above composite oil phase was slowly added dropwise to the emulsified aqueous phase. Emulsification was continued for 40 min to obtain a stable milky white composite emulsion. The emulsion was covered and allowed to stand for 5 h to remove bubbles, so as to reduce premature hydrolysis caused by the moisture absorption of tetraethyl orthosilicate.
[0055] (4) Double cross-linking encapsulation. The composite emulsion was added to the polyvinyl alcohol / sodium alginate precursor solution and mixed evenly. Then, it was added dropwise to an 8% calcium chloride solution to allow Ca to form encapsulation. 2+ The microcapsules underwent a primary ionic crosslinking with alginate to form hydrogel particles. The resulting gel beads were then transferred to a 7% boric acid solution for secondary crosslinking, and the pH of the system was adjusted to 8 using a 1.0 mol / L sodium hydroxide solution. The reaction was maintained at 20 °C with gentle stirring. After the secondary crosslinking was complete, the microcapsules were collected, washed three times with deionized water, and dried at room temperature for later use.
[0056] Example 4
[0057] This embodiment provides a method for preparing cement paste specimens, using 40 mm × 40 mm × 40 mm cement paste specimens with a water-cement ratio of 0.50. A blank control group (CG) without microcapsules, an OMG group with ordinary microcapsules, and an SMG group with self-filled microcapsules were set up; the microcapsule dosage of OMG and SMG was 0.5% of the cement mass. During preparation, cement and the corresponding microcapsules were first dry-mixed, then mixing water was added and mechanically stirred; after uniform mixing, the mixture was molded, demolded after 24 hours, and cured in a standard curing environment of 20±2 ℃ and relative humidity not less than 95% until the corresponding age was reached.
[0058] like Figure 2 As shown, both conventional microcapsules and self-filled microcapsules retain the main structural features of polyvinyl alcohol / sodium alginate double crosslinked hydrogels. The self-filled microcapsules have a crosslinking density of 1000-1100 cm⁻¹. -1 Enhanced silicon-oxygen related absorption within the range, and the broad peak at approximately 20° in the X-ray diffraction pattern further broadened and flattened, indicating that the introduction of tetraethyl orthosilicate increased the amorphous silicon-containing structure. Energy dispersive spectroscopy (EDS) results showed that the silicon mass fraction in the self-filled microcapsules was 32.9%, higher than the 24.1% in ordinary microcapsules, proving that tetraethyl orthosilicate had been successfully introduced into the microcapsule system and provided a material basis for the subsequent formation of silicon-oxygen-containing structures and local self-filling.
[0059] like Figure 3As shown, the contact angle of the CG group remained at approximately 33° for 35 days, maintaining significant hydrophilicity. The contact angles of both the OMG and SMG groups exhibited an S-shaped growth: the initial growth was slow, the rate of increase accelerated after about 10 days, and gradually stabilized after 30 days. The contact angle of the SMG group gradually increased from an initial 32.0° to 117.5°, close to the final contact angle of the OMG group (118.2°), indicating that the introduction of tetraethyl orthosilicate did not weaken the overall hydrophobic effect provided by hydroxyl-terminated polydimethylsiloxane in the later stages.
[0060] like Figure 4 As shown, with increasing curing age, hydroxyl-terminated polydimethylsiloxane gradually establishes a hydrophobic layer, and the silicon-oxygen-containing structure formed by tetraethyl orthosilicate compensates for micropores and local defects, resulting in SMG exhibiting progressively lower chloride ion penetration depths at 14 and 28 days. At 28 days, the penetration depth of SMG was 3.6 mm, which was approximately 7.69% and 25% lower than that of OMG and CG, respectively.
[0061] like Figure 5 As shown, at 60 days, the porosity of SMG decreased by 13.49% compared to OMG. Ordinary microcapsules, as added particles, occupy slurry space and form new interface regions; residual cavities are also formed after the core material is released. This indicates that the silicon-oxygen-containing structure formed by self-filled microcapsules in a strongly alkaline and humid environment can compensate for some of the porosity defects caused by the introduction of ordinary microcapsule particles, interface mismatch, and core material release.
[0062] like Figure 6 As shown, the three-dimensional reconstruction results of X-ray computed tomography (CT) scans reveal that the CG group has the fewest internal defects and their distribution is relatively dispersed, while the OMG group shows a significant increase in the number of defect points and dense clustering in local areas. The SMG group has a defect number and clustering degree between CG and OMG, and its local high-density defects are significantly less than those in the OMG group. These results further demonstrate, from a spatial distribution perspective, that the self-filled composite core material can provide structural compensation for local defects around the microcapsules and near the release path in the mid-to-late stages.
[0063] like Figure 7 As shown, at 90 days, the strength loss of SMG relative to CG was only 2.6%, recovering approximately 56.1% of the strength loss caused by the introduction of ordinary microcapsules. This mid-to-late stage strength compensation is consistent with the gradual filling of the interface region and local pores around the microcapsules by the tetraethyl orthosilicate-derived silicon-containing structure.
[0064] The above embodiments demonstrate that the key to this invention is not simply the superposition of hydrophobic release and pore filling, but rather the realization of structure-function synergy that occurs sequentially through early isolation of the double cross-linked capsule wall, mid-term hydrophobic migration of hydroxyl-terminated polydimethylsiloxane, and late-term silicon-containing structure compensation of tetraethyl orthosilicate.
Claims
1. A self-filled hydrophobic hydrogel microcapsule, characterized in that, The microcapsule includes a core material and a capsule wall covering the core material; the capsule wall is a hydrogel network formed by double crosslinking of polyvinyl alcohol and sodium alginate, and the core material is a composite core material composed of hydroxyl-terminated polydimethylsiloxane and tetraethyl orthosilicate.
2. A method for preparing self-filled hydrophobic hydrogel microcapsules, characterized in that, Includes the following steps: Step 1: Mix polyvinyl alcohol aqueous solution and sodium alginate aqueous solution thoroughly to obtain polyvinyl alcohol / sodium alginate hydrogel precursor solution; Step 2: Mix hydroxyl-terminated polydimethylsiloxane with tetraethyl orthosilicate until homogeneous to obtain a hydrophobic-self-filled composite oil phase; Step 3: Add emulsifier to water to form an emulsified aqueous phase. Under stirring conditions, add the composite oil phase dropwise to the emulsified aqueous phase for emulsification to obtain a composite emulsion. Step 4: Add the composite emulsion to the hydrogel precursor solution and mix evenly to obtain a capsule-forming precursor solution containing the composite core material. Step 5: Add the capsule-forming precursor solution dropwise into the calcium chloride solution, allowing sodium alginate to pass through the Ca... 2+ Hydrogel microbeads are formed through primary ionic cross-linking. Step 6: Transfer the hydrogel microbeads to a boric acid solution to allow polyvinyl alcohol to undergo secondary cross-linking. Then collect, wash and dry to obtain the self-filled hydrophobic hydrogel microcapsules.
3. The method for preparing self-filled hydrophobic hydrogel microcapsules according to claim 2, characterized in that, In step 1, the dry basis mass ratio of polyvinyl alcohol to sodium alginate is 1:1-4:
1.
4. The method for preparing self-filled hydrophobic hydrogel microcapsules according to claim 2, characterized in that, In step 2, the mass ratio of hydroxyl-terminated polydimethylsiloxane to tetraethyl orthosilicate is 92:8-100:
10.
5. The method for preparing self-filled hydrophobic hydrogel microcapsules according to claim 4, characterized in that, In step 2, hydroxyl-terminated polydimethylsiloxane is mixed with tetraethyl orthosilicate at 15-35 ℃ and 100-800 r / min for 1-30 min.
6. The method for preparing self-filled hydrophobic hydrogel microcapsules according to claim 2, characterized in that, In step 3, the emulsifier is alkylphenol polyoxyethylene ether.
7. The method for preparing self-filled hydrophobic hydrogel microcapsules according to claim 2, characterized in that, In step 5, the mass concentration of the calcium chloride solution is 4%-8%.
8. The method for preparing self-filled hydrophobic hydrogel microcapsules according to claim 1, characterized in that, In step 6, the mass concentration of the boric acid solution is 3%-7%.
9. A cement-based material, characterized in that, Contains the self-filled hydrophobic hydrogel microcapsules as described in claim 1.
10. A method for preparing the cement-based material according to claim 9, characterized in that, The gelling material and the microcapsules are first dry-mixed, then mixed with water and mechanically stirred, and then cured after molding.